MANAJEMEN LABA SETELAH PENURUNAN PERINGKAT OBLIGASI PERUSAHAAN - Dewi, Made Karunia; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2015)
Bond ratings downgrade reflect the conditions and credibility of the company that is on the decline. The downgrade of these bonds will result in a negative perception of investors about the credit quality of the bonds. This has encouraged the management company in the hope of earning management berkutnya period bond ratings could increase. Previous research states that the bond downgrade will trigger companies doing earnings management that increase profitability. Retrieved 60 sample companies which decreased bond ratings by purposive sampling method. Model Kothari (2005) is used to identify companies that perform earnings management practices. Hypothesis testing using Independent Sample T Test. Conclusion this study is a company that has decreased bond rating (downgrade) perform earnings management by increasing the amount of discretionary accruals earnings when publishing the audited financial statements after a period of decline in bond ratings.
Keywords: Earnings Management, Bond Ratings Downgrade, Discretionary Accrual